Dinitrile-Assisted Electrolyte Helps Overcome Temperature Challenges of Lithium Batteries - Mengqi Wu; Shengyao Luo; Tonghui Xu; Tianle Zheng; Zhengzheng Ru; Said Amzil; Yiyao Xiao; Yinghui Li; Meilan Peng; Wenwen Xue; Jie Gao; Yunfang Gao; et al. (Energy Material Advances)
Lithium metal batteries (LMBs) have attracted much attention due to their high specific capacity. However, commercial carbonate electrolytes are challenging to apply in LMBs because of the narrow operating temperature range (−20 to 50 °C). Carboxylate solvents have the advantages of low viscosity and low freezing point and perform well at low temperatures. However, their poor thermal stability limits their application at high temperatures. This work added a dinitrile solvent to the carboxylate electrolyte to expand its liquid range and improve its electrochemical stability. In addition, the coordination of molecules in the first solvated layer is carefully controlled to promote many anions entering the solvated layer, contributing to forming a robust inorganic solid electrolyte interface film. Because of the addition of the dinitrile solvent, the electrolyte enables Li/NCM811 cells to achieve a capacity release of 149.3 mAh/g at −40 °C. After 200 cycles at 80 °C, the capacity retention rate of Li/LFP cells is 94.31%. Even in ultra-thin lithium metal cells (17 μm), it can be stable for more than 100 cycles. This opens up new opportunities for developing electrolytes suitable for high-performance and all-weather LMBs.